Abdominal Obesity, Dyslipidemia and Blood Pressure - Pedro Enrique Miguel Soca (Revista Finlay, 2015)
Fat stored in the abdominal region is resistant to insulin, increased degradation of triglycerides to fatty acids. The increased availability of fatty acids in the liver favors the formation of very low density lipoproteins and the resulting hypertriglyceridemia alters the pattern of lipoproteins with an elevation of low density lipoproteins, and dense small and a decrease of high density lipoproteins.